2021
DOI: 10.1080/11287462.2021.1966974
|View full text |Cite
|
Sign up to set email alerts
|

Free healthcare for some, fee-paying for the rest: adaptive practices and ethical issues in rural communities in the district of Boulsa, Burkina Faso

Abstract: In Burkina Faso, in July 2016, user fees were removed at all public healthcare facilities, but only for children under 60 months of age and for “mothers”, i.e. for reproductive care. This study was conducted in five rural communities in Boulsa District (Burkina Faso) (1) to understand the perceptions and practices of stakeholders regarding compliance with eligibility criteria for free care and (2) to explore the ethical tensions that may have resulted from this policy. Semi-directed individual interviews ( … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 53 publications
0
3
0
Order By: Relevance
“…The desired uptake would have not been achieved [27]. Targeting segments of the population (children under 5 years of age, patients 5 years old and above, and pregnant women) is part of the health system routine practices, and hence was the most viable option [31]. Indeed, when introducing a national free healthcare policy for children under 5 and pregnant women, HWs adapted their practices accordingly [31].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The desired uptake would have not been achieved [27]. Targeting segments of the population (children under 5 years of age, patients 5 years old and above, and pregnant women) is part of the health system routine practices, and hence was the most viable option [31]. Indeed, when introducing a national free healthcare policy for children under 5 and pregnant women, HWs adapted their practices accordingly [31].…”
Section: Discussionmentioning
confidence: 99%
“…The distribution and availability of antimalarials for the three segments, as well as their relatively low cost (as subsidized), were highly appreciated by the populations. Many studies have previously reported that the removal of financial barriers to health services use increases communities' attendance at PHF for care [31,37]. Regardless of the MFT option selected, subsidizing the cost of ACTs should be used to reduce affordability issues.…”
Section: Discussionmentioning
confidence: 99%
“…Burkina Faso has a fee-based healthcare system that uses out-of-pocket payments, although pregnant women and children under five receive free health care and medications. 29 As a result, human landing catch participants diagnosed with malaria after the 21-day period observed by Target Malaria would be responsible for paying for healthcare and medications themselves.…”
Section: Target Malaria In Burkina Fasomentioning
confidence: 99%